2017
DOI: 10.1590/1807-7692bar2017170048
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap: Lessons from the UK to Brazil about the Roles of TTOs throughout Collaborative R&D Projects

Abstract: The literature about collaboration for innovation has reported fundamental activities performed by intermediaries. In this paper, universities' technology transfer offices (TTOs) are placed as intermediaries between academic research and the industry. Our study focuses on collaborative research and development (R&D) projects between universities and industry in order to understand the roles of TTOs throughout the whole duration of the project. The main aim of this paper is to identify the roles of TTOs through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 58 publications
0
13
2
Order By: Relevance
“…• Intermediation: in contrast to findings in recent literature (De Silva et al, 2017;Thomas et al, 2017), where intermediaries are external agents providing services for inter-organizational R&D projects, our research showed relationships intermediated by other departments of the firms. Relationships with external partners were not directly connected to R&D staff: relationships with suppliers occur through supply/purchasing departments in both firms.…”
Section: Changes Of Internal Practicescontrasting
confidence: 99%
See 1 more Smart Citation
“…• Intermediation: in contrast to findings in recent literature (De Silva et al, 2017;Thomas et al, 2017), where intermediaries are external agents providing services for inter-organizational R&D projects, our research showed relationships intermediated by other departments of the firms. Relationships with external partners were not directly connected to R&D staff: relationships with suppliers occur through supply/purchasing departments in both firms.…”
Section: Changes Of Internal Practicescontrasting
confidence: 99%
“…Open innovation points to the emergence of intermediaries of relationships that are non-existent in closed innovation or have irrelevant roles (De Silva et al, 2017;Howells, 2006;Thomas et al, 2017). Innovation brokers allow firms to transact, at stages previously conducted within the firm, by connecting those seeking solutions with a rather large number of potential knowledge suppliers (Kock & Gözübüyük, 2011).…”
Section: From Closed To Open Innovation In Emerging Economies: Evidenmentioning
confidence: 99%
“…• Intermediation: in contrast to findings in recent literature (De Silva et al, 2017;Thomas et al, 2017), where intermediaries are external agents providing services for inter-organizational R&D projects, our research showed relationships intermediated by other departments of the firms. Relationships with external partners were not directly connected to R&D staff: relationships with suppliers occur through supply/purchasing departments in both firms.…”
Section: Changes Of Internal Practicescontrasting
confidence: 99%
“…Open innovation points to the emergence of intermediaries of relationships that are non-existent in closed innovation or have irrelevant roles (De Silva et al, 2017;Howells, 2006;Thomas et al, 2017). Innovation brokers allow firms to transact, at stages previously conducted within the firm, by connecting those seeking solutions with a rather large number of potential knowledge suppliers (Kock & Gözübüyük, 2011).…”
Section: From Closed To Open Innovation In Emerging Economies: Evidenmentioning
confidence: 99%
“…Sustainable human resources development and knowledge sharing as part of relationship capital [83] enables companies to manage their adaptation to Industry 4.0 [84][85][86] and grant them the "how to do" expertise in this process. Openness towards external knowledge sources [87] and partnerships [88] in training enables firms to access the knowledge in developing appropriate procedures and solutions required for Industry 4.0 transition. Also, according to the research by Götz and Jankowska [89], these challenges will drive companies to assure network embeddedness and to collaborate, share risks, and jointly learn.…”
Section: Discussionmentioning
confidence: 99%